2022
DOI: 10.1039/d2nj04414e
|View full text |Cite
|
Sign up to set email alerts
|

A photocatalyst-free method for the synthesis of 6-alkyl(aryl)phenanthridines under visible light irradiation

Abstract: A novel and effective blue LEDs-induced methodology has been developed to synthesize a number of 6-alkyl(aryl)phenanthridines from isocyanobiaryls and alkyl(aryl)sulfinates in ethyl lactate under aerobic conditions. This protocol did not...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…When sodium 4methylbenzenesulfinate was replaced with 4-methylbenzenesulfinic acid (2a), the yield of the product 3a increased to 39% (Table 1, entry 13). To further improve the yield, we looked at the stoichiometry of 2a with respect to substrate 1a (Table 1, entries [14][15][16][17]. The best outcomes were obtained when 1a and 2a were combined in a 1 : 3 ratio, cf.…”
Section: Resultsmentioning
confidence: 99%
“…When sodium 4methylbenzenesulfinate was replaced with 4-methylbenzenesulfinic acid (2a), the yield of the product 3a increased to 39% (Table 1, entry 13). To further improve the yield, we looked at the stoichiometry of 2a with respect to substrate 1a (Table 1, entries [14][15][16][17]. The best outcomes were obtained when 1a and 2a were combined in a 1 : 3 ratio, cf.…”
Section: Resultsmentioning
confidence: 99%
“…32 Upon exposure to blue LED light, the reaction of 4a with methylhydrazine hydrochloride in the presence of eosin B at room temperature, as well as blue LED-induced cyclisation in the absence of a photocatalyst with sodium methanesulnate under aerobic conditions, yielded a mixture of pyrroloquinoxaline 5a and 6a (entries 5 and 6). 33,34 Using Fenton reaction conditions reported by Zhang led exclusively to the formation of bis-methyl pyrroloquinoxaline 6a (entry 7). 35 Encouraged by these results of selectively being able to favour mono-methyl radical addition over bis-methylation, these conditions were initially investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Exploiting the formation of an EDA complex between alkyl(aryl)sulfinates 44 and isocyanobiaryls 43, Natarajan et al reported a methodology for the preparation of 6alkyl(aryl)phenanthridines 45 in ethyl lactate under aerobic conditions (Scheme 16). [31] 24 products were synthesized with yields between 39 and 74 %. The reaction was also scaled-up to 7 mmol with a yield of 72 %.…”
Section: Additive-free Methodologies Involving Eda Complexesmentioning
confidence: 99%